The Traditional Karonese Oil as Ancestral Heritage - Sari, Ellieka; Sitepu, Runtung; Saidin; Maria (International Journal of Culture and Art Studies, 2023)
Every indigenous people are familiar with traditional medicine and medical techniques in order to maintain life in an atmosphere of support for community medicine and medical techniques. Traditional knowledge, especially traditional medicine, is Karonese Oil which has important benefit. This study examines the openness of the ancestral heritage of traditional knowledge of Karonese Oil. In this study, it is hoped that a renewal of regulations on traditional knowledge is closely related to regulations on the protection of traditional medicine because of medicine and techniques that have not received adequate legal protection. Data collection is carried out descriptive qualitative research, descriptive is a problem formulation that guides research to explore or portray the social situation to be studied thoroughly, broadly and in depth to craftsmen or traditional Karo oil activists.Â  The data were analyzed qualitatively by using a legal theory approach as a rationale. Indigenous peoples rule on the protection of traditional knowledge of ancestral heritage of traditional Karo tribe oil. The Karonese tribe has various kinds of knowledge of medicine and traditional medicine techniques, especially Karonese oil. Updating on traditional knowledge that are closely related to regulations on the protection of traditional medicine due to inadequate medicines and techniques. This is in the form of regulations concerning the draft law on the protection and use of intellectual property, traditional knowledge and traditional cultural expressions, which until now have not been ratified by the Government.